Analisis Kelayakan dan Kepraktisan Modul Praktikum Berbasis Literasi Sains untuk Pembelajaran IPA - Nur Samsu; Dona Mustika; Rizky Nafaida; Nurhasnah Manurung (Universitas Syiah Kuala, 2020)
Practicum modules are needed during the practical learning process activities that can be used by teachers and students. Science literacy must be mastered by students, because it is related to the environment. Science literacy is assessed from three aspects namely content, process and context. The purpose of this study was to determine the feasibility test and practical test of practicum modules based on science literacy for science learning in SMP Negeri 1 Langsa. This type of research is research and development which is modified into three stages of research implementation with the module trial stage developed in the form of research and information gathering, module design phase and module development stage with documentary study data collection techniques, questionnaires, and experiments. The scores obtained will be processed using descriptive analysis by conducting a feasibility test by material and media experts consisting of biology education lecturers while the practicality test uses a questionnaire distributed to students of class VIII at SMP Negeri 1 Langsa on Natural Sciences subjects. The results showed that the IPA practicum product modules analyzed consisted of three categories: the percentage value of the highly valid aspects with a value of 78% on the module quality element, while the practicality test consisted of three aspects namely the content, process and context aspects of the results of the three aspects. The percentage value of 82.8% of the aspects of positive student response content that practicum modules are used is very practical. Based on the values obtained that the IPA practicum module is feasible and practically used as a practical guide.